CLINICAL EFFICACY AND SAFETY OF SEIZING PAROXYSMS OF ATRIAL FIBRILLATION WITH PROPAPHENON - A. Zakhar; I. V. Antonchenkov; E. V. Borisova; S. V. Popov; I. O. Kurlov (Российский кардиологический журнал, 2003)
The study was made to evaluate clinical efficacy, safety and electrophysiological effects of Propaphenon in seizing paroxysms of atrial fibrillation (AF)45 patients have been evaluated, with AF paroxysms lasting up to 48 hours. To restore sinus rhythm (SR) single oral intake of 600 mg Propaphenon (PRO. MED. CS Praha a.s. ) was used. AF paroxysms were seized under the control of ECG Hotter and BP monitoring.Antiarrhythmic effect was evaluated based on the results of dynamics of electrophysiological parameters determined by means of transesophageal heart electrophysiology studies (ТЕ EPS) in 12 patients.A comparative analysis of results obtained has shown that Propanorm is an effective antiarrhythmic drug to treat AF paroxysms. Heart sinus rhythm (SR) restoration takes place in 88. 9 % cases whereas electrophysiological criteria for antiarrhythmic response include: increased value of rate threshold of induction (RTI) by 140 impulses per minute, disappearance of atrial vulnerability zone and prolonged AV node effective refractory period by 50 ms.